Global observations of magnetospheric high‐m poloidal waves during the 22 June 2015 magnetic storm. Issue 8 (24th April 2017) - Le, G.; Chi, P. J.; Strangeway, R. J.; Russell, C. T.; Slavin, J. A.; Takahashi, K.; Singer, H. J.; Anderson, B. J.; Bromund, K.; Fischer, D.; Kepko, E. L.; Magnes, W.; et al.
Abstract: We report global observations of high‐ m poloidal waves during the recovery phase of the 22 June 2015 magnetic storm from a constellation of widely spaced satellites of five missions including Magnetospheric Multiscale (MMS), Van Allen Probes, Time History of Events and Macroscale Interactions during Substorm (THEMIS), Cluster, and Geostationary Operational Environmental Satellites (GOES). The combined observations demonstrate the global spatial extent of storm time poloidal waves. MMS observations confirm high azimuthal wave numbers ( m  ~ 100). Mode identification indicates the waves are associated with the second harmonic of field line resonances. The wave frequencies exhibit a decreasing trend as L increases, distinguishing them from the single‐frequency global poloidal modes normally observed during quiet times. Detailed examination of the instantaneous frequency reveals discrete spatial structures with step‐like frequency changes along L . Each discrete L shell has a steady wave frequency and spans about 1  R E, suggesting that there exist a discrete number of drift‐bounce resonance regions across L shells during storm times. Key Points: Observed long‐lasting high‐ m poloidal waves associated with second harmonics of field line resonances during a major magnetic storm Demonstrated global spatial extent of storm time poloidal FLR region using observations from a constellation of widely spaced satellites Revealed discrete spatial structures of resonant L shells with step‐like frequency changes